Preparation method of SiC fiber reinforced aluminum-based composite material

By preparing SiCf/2024Al precursor fibers through sputtering and segmented hot isostatic pressing processes, the problems of fiber breakage and interfacial reaction in SiC fiber-reinforced aluminum matrix composites were solved, and the preparation of high-strength SiC fiber-reinforced aluminum matrix composites was realized to meet the needs of high-end equipment.

CN120967258AActive Publication Date: 2025-11-18INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202511517286.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2025-11-18
Estimated Expiration
2045-10-23

AI Technical Summary

Technical Problem

In the existing preparation process of SiC fiber-reinforced aluminum matrix composites, the fibers are prone to breakage, the interfacial reaction products are uneven, and the fiber arrangement is uneven, which leads to a decline in material performance and makes it difficult to meet the high strength requirements of high-end equipment.

Method used

SiCf/2024Al precursor fibers were prepared by sputtering. By controlling the sputtering parameters and slow cooling rate, combined with segmented hot isostatic pressing, a gradient carbon layer and 2024Al alloy cladding were designed to ensure uniform fiber arrangement and enhanced interfacial bonding, and to avoid the formation of brittle phases.

Benefits of technology

The SiC fiber reinforced aluminum matrix composite material achieved a room temperature tensile strength ≥1400MPa, a room temperature compressive strength ≥3000MPa, and a 200℃ compressive strength ≥2300MPa, significantly improving the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120967258A_ABST
    Figure CN120967258A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloy composite materials, in particular to a preparation method of a SiC fiber reinforced aluminum matrix composite material. Carrying out hot isostatic pressing treatment on the sheath and the precursor wire, heating the sheath and the precursor wire to 400-500 DEG C at a heating rate of 4-7 DEG C / min, and keeping the temperature and the pressure under the pressure of 80-130 MPa; then cooling to 200 DEG C along with the furnace, maintaining the pressure of 80-130 MPa, and keeping the temperature and pressure; continuously cooling to 100 DEG C along with the furnace, adjusting the pressure to 100 MPa, and keeping the temperature and the pressure; and finally, cooling to room temperature along with the furnace to obtain the SiC fiber reinforced aluminum-based composite material. According to the preparation method, the problems that fibers are broken in advance, interface reaction products are uneven, failure is prone to occurring, and fiber arrangement is uneven in the existing SiC fiber reinforced aluminum matrix composite material preparation process are solved, and the SiC fiber reinforced aluminum matrix composite material with high tensile strength and high compressive strength at room temperature and high compressive strength at 200 DEG C is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy composite materials technology, and in particular to a method for preparing SiC fiber reinforced aluminum matrix composite materials, which is applicable to fields such as aerospace and transportation where high-temperature strength and lightweight materials are required. Background Technology

[0002] Aluminum alloys possess characteristics such as low density, high specific strength, good corrosion resistance, and ease of processing, making them promising for applications in aerospace, transportation, and machinery manufacturing. As a primary metallic material in aircraft manufacturing, aluminum alloys account for over 70% of the materials used in aircraft like the B777 and A380. In my country's domestically developed C919 large passenger aircraft, aluminum alloys also account for over 60% of the material. With the global aviation industry's increasing demand for high-strength and lightweight materials, the development of high-performance aluminum-based composite materials has become a current focus.

[0003] Among various aluminum matrix composites, fiber-reinforced aluminum matrix composites exhibit outstanding lightweight and high strength characteristics. Common fiber reinforcements include SiC fibers, B fibers, C fibers, and glass fibers. Among these, SiC fibers, with their high strength, high stiffness, and high temperature resistance, are considered an important reinforcement in fiber-reinforced aluminum matrix composites.

[0004] However, the preparation of high-performance SiC fiber-reinforced aluminum matrix composites still faces many technical bottlenecks. For example, traditional preparation processes such as powder metallurgy require high-energy ball milling to mix the fibers and matrix. During this process, SiC fibers are prone to breakage or surface damage due to mechanical impact, leading to deterioration of the reinforcing phase properties. Secondly, although liquid metal infiltration methods (such as pressure infiltration and pressureless infiltration) can achieve effective bonding between fibers and the matrix, the wettability between aluminum melt and SiC fibers is poor, and interfacial reactions (such as the formation of brittle Al4C3 phase) are prone to occur at high temperatures. The interfacial products are difficult to control, which will affect the interfacial bonding strength and reduce the service life of the material. In addition, the fiber arrangement is also an important factor affecting aluminum matrix composites. Insufficient control of fiber uniformity can easily lead to local agglomeration or disordered orientation, resulting in uneven stress on the aluminum matrix composite and thus reducing the performance of the composite material.

[0005] Patent CN114525434A discloses a SiC-induced multiphase reinforced aluminum matrix composite material and its preparation method. It uses nano-SiC particles for reinforcement, but relies on selective laser melting for forming, which leads to particle agglomeration. Local high temperatures can still generate hard and brittle phases, resulting in decreased material toughness and a maximum tensile strength of only 445 MPa, far below the requirements for applications. Patent CN116695031A discloses a manufacturing equipment and method for continuous SiC fiber reinforced Al-based composite filaments. It uses an ultrasonic-assisted liquid-phase infiltration method to achieve continuous fiber preparation, but relies on high tension control, resulting in a high risk of fiber abrasion against the equipment's hole walls. Furthermore, the aluminum melt temperature reaches 680-880℃, making the fibers prone to surface damage at high temperatures. Ultimately, the composite filament's tensile strength is only 1200 MPa, which is insufficient to meet the requirements of high-end equipment. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing SiC fiber-reinforced aluminum matrix composites, which solves the problems of premature fiber breakage, uneven interfacial reaction products, easy failure, and uneven fiber arrangement in the current preparation process of SiC fiber-reinforced aluminum matrix composites, and obtains SiC fiber-reinforced aluminum matrix composites with high tensile strength and high compressive strength at room temperature and high compressive strength at 200℃.

[0007] The technical solution of this invention is: A method for preparing SiC fiber-reinforced aluminum matrix composite material includes the following steps: Step 1: Preparation of SiC f / 2024Al precursor wire: using rolled 2024Al as the target material, the total content of Mn, Si, and Fe impurities in the target material is controlled to be <1wt%, and the α-Al grain size in the target material is <50μm. 2 Equiaxed crystals; before sputtering, the SiC fiber substrate is heated to 200~400℃ and evacuated to a pressure of 2×10⁻⁶. -4 ~9×10 -4 Pa; SiC fiber substrates were sputtered using a sputtering current of 1–4 A and a sputtering voltage of 290–340 V, controlling the total thickness of the sputtered 2024Al alloy matrix to be 20–29 μm, so that the α-Al grain size in the pre-sputtered wire was <20 μm. 2 After sputtering, the material is cooled to room temperature at a rate of 2~5℃ / min. Step 2, Sheath Assembly and Packaging: Using 2024Al alloy as the sheath material, the pilot wire obtained in Step 1 is cut into equal-length segments, each segment being 4-8 mm shorter than the sheath and the length difference between individual pilot wires being <1 mm. After the pilot wires are inserted into the sheath, the sheath cap is sealed using vacuum electron beam welding. The welding material is high-purity 2024Al alloy with an impurity content of <0.5 wt%, and the SiC fiber volume fraction is controlled at 50% ± 5%. Step 3, Segmented Hot Isostatic Pressing: The composite material encapsulated in Step 2 is heated to 400-500℃ at a heating rate of 4-7℃ / min and held at 80-130MPa for 3-5 hours; then cooled to 200℃ in the furnace and held at 80-130MPa for 0.5-2 hours; then cooled to 100℃ in the furnace and held at 100MPa for 0.5-2 hours; finally cooled to room temperature in the furnace to obtain SiC fiber reinforced aluminum matrix composite material.

[0008] In the preparation method of the SiC fiber reinforced aluminum matrix composite material, in step one, the composition of the 2024Al alloy matrix obtained on the surface of SiC fiber after sputtering is as follows (by mass percentage): Cu 3~5%, Mg 1~2%, Mn 0~0.7%, Si 0~0.5%, Fe 0~0.3%, with Al as the balance.

[0009] The preparation method of the SiC fiber reinforced aluminum matrix composite material, by mass percentage, has the following composition of 2024Al alloy matrix: Cu 3.5~4.5%, Mg 1.2~1.8%, Mn 0~0.5%, Si 0~0.3%, Fe 0~0.1%, with Al as the balance.

[0010] In the preparation method of the SiC fiber reinforced aluminum matrix composite material, in step one, a carbon layer with a thickness of 1~3μm is provided on the surface of the SiC fiber. The carbon layer is located between the SiC fiber and the 2024Al alloy matrix. The side closer to the SiC fiber is a pyrolytic carbon layer containing nano-sized silicon carbide particles. The mass ratio of silicon carbide particles in the carbon layer is 5~15%. The side closer to the 2024Al alloy matrix is ​​a pyrolytic carbon layer.

[0011] In the preparation method of the SiC fiber reinforced aluminum matrix composite material, in step two, the diameter of the sheath is 3~4mm, the thickness is 0.3~0.65mm, the pore size is 2.4~2.9mm, the size of the sheath increases accordingly as the size of the aluminum matrix composite material increases, and the volume fraction of SiC fiber is 50%.

[0012] The preparation method of the SiC fiber reinforced aluminum matrix composite material is described above. In the SiC fiber reinforced aluminum matrix composite material, the 2024Al alloy matrix structure and the 2024Al alloy cladding structure are uniform. There is an amorphous carbon layer with a thickness of 10~50nm between the carbon layer and the 2024Al alloy matrix, and there are no Al4C3 reaction products.

[0013] The preparation method of the SiC fiber-reinforced aluminum matrix composite material, after hot isostatic pressing, results in a 2024Al alloy matrix microstructure and a 2024Al alloy cladding microstructure both consisting of alternating fine equiaxed α-Al, Al2Cu, and Al2CuMg phases. fThe 2024Al precursor fibers are evenly distributed in a hexagonal pattern, with no SiC fiber breakage.

[0014] The design concept of this invention is: This invention employs a sputtering process to fabricate SiCf / 2024Al precursor wires. By adjusting the sputtering current (1~4A), voltage (290~340V), and substrate temperature (200~400℃), the α-Al grain size in the precursor wire is precisely controlled to 20μm. 2 Furthermore, a slow cooling rate of 2~5℃ / min is used to reduce residual stress and prevent fiber breakage due to mechanical impact or thermal stress during the preparation stage. In addition, the size scheme of the 2024Al alloy sheath and the pilot wire is designed (such as a small-sized rod-shaped composite material sheath with a diameter of 3~4mm and a hole diameter of 2.4~2.9mm), and the pilot wire is cut to the same length (length difference <1mm) to ensure that the fibers are evenly arranged in hexagons after being put into the sheath, thus solving the problem that continuous fibers are prone to disordered arrangement due to tension fluctuations.

[0015] This invention employs a segmented hot isostatic pressing process for the sheath and the pilot wire, heating them to 400-500℃ at a slow heating rate of 4-7℃ / min, and then gradually cooling them by holding them at 400-500℃ → 200℃ → 100℃. This avoids localized high-temperature concentration, ultimately resulting in only a 10-50nm amorphous carbon transition layer between the carbon layer and the 2024Al alloy matrix. This completely suppresses the formation of other brittle phases and solves the problem of decreased plasticity and toughness caused by brittle phases at the interface. In addition, during the segmented hot isostatic pressing process, the pressure of 80~130MPa and the temperature gradient work together to ensure that there is no air residue in the casing, so that the material density meets the high performance requirements. On the other hand, the matrix structure is controlled to be fine equiaxed crystals with alternating distribution of α-Al, Al2Cu and Al2CuMg phases. Through the coupling of fine grain strengthening and second phase strengthening, the performance breakthrough of room temperature tensile strength ≥1400MPa, room temperature compressive strength ≥3000MPa and 200℃ compressive strength ≥2300MPa is finally achieved.

[0016] This invention designs a gradient carbon layer with a thickness of 1~3μm on the surface of the precursor fiber, and uniformly disperses nano-SiC particles in the pyrolytic carbon on the side close to the SiC fiber, which structurally prevents the direct reaction between the 2024Al alloy matrix and the SiC fiber; the side close to the 2024Al alloy matrix is ​​made of high-purity pyrolytic carbon, which ensures a tight bond between the 2024Al alloy matrix and the carbon layer.

[0017] The advantages and beneficial effects of this invention are: 1. This invention uses SiC f High-performance SiC is prepared by using 2024Al precursor wire as the core material, encasing it in a 2024Al alloy sheath, followed by vacuuming, electron beam welding, and a specific hot isostatic pressing process.f / 2024Al composite material is used to solve the problem of low strength of aluminum alloy under high temperature conditions. The resulting composite material has no broken fibers and is uniformly arranged in equal hexagonal shapes, avoiding the problem of uneven stress caused by fiber agglomeration or disordered orientation in traditional processes. There are no Al4C3 reaction products in the interface reaction layer, and the interface is connected by amorphous carbon.

[0018] 2. The gradient carbon layer (high-purity pyrolytic carbon and pyrolytic carbon containing nano-SiC) of the precursor wire of this invention works synergistically with segmented hot isostatic pressing to form only a 10~50nm amorphous carbon transition layer between the carbon layer and the 2024Al alloy matrix, reducing the formation of brittle phases, improving interfacial bonding and increasing the service life of the material.

[0019] 3. This invention controls the α-Al grain size of the precursor wire to <20μm through a sputtering process. 2 Hot isostatic pressing (HIP) regulates the matrix microstructure to produce fine equiaxed crystals, resulting in composite materials with excellent room temperature strength and high-temperature compressive strength. (SiC) f The room temperature tensile strength of the 2024Al composite material is above 1400MPa, the room temperature compressive strength is above 3000MPa, and the 200℃ compressive strength is above 2300MPa, which is significantly better than the room temperature and high temperature mechanical properties of existing SiC reinforced aluminum matrix composite materials. Attached Figure Description

[0020] Figure 1 This is a dimensional diagram of a rod-shaped tensile specimen.

[0021] Figure 2 The diagram shows the dimensions of a rod-shaped compression specimen. (a) is a cross-sectional view of the specimen, (b) is a side view of the specimen, and (c) is a view of SiC. f / Cross-section diagram of 2024Al precursor wire. Labels in the diagram: 1-2024Al alloy sheath, 2-SiC f / 2024Al precursor fiber (21-SiC fiber, 22-2024Al alloy matrix, 23-carbon layer).

[0022] Figure 3 The microstructure of the 2024Al alloy cladding is shown.

[0023] Figure 4 The result is a room temperature load displacement stretch curve.

[0024] Figure 5 This is a room temperature load-displacement compression curve.

[0025] Figure 6 The load-displacement compression curve is shown at 200℃. Detailed Implementation

[0026] In the specific implementation process, such as Figure 2 As shown, SiCf The 2024Al precursor wire 2 comprises SiC fiber 21, a 2024Al alloy substrate 22, and a carbon layer 23 between them. The carbon layer 23 has a thickness of 1~3μm. The side closer to the SiC fiber 21 is a pyrolytic carbon layer containing nanoscale silicon carbide particles, and the side closer to the 2024Al alloy substrate 22 is a high-purity (99.99wt%) pyrolytic carbon layer. The mass ratio of silicon carbide particles in the carbon layer 23 is 5~15%. The preparation process of the pyrolytic carbon layer is as follows: SiC is deposited simultaneously with the carbon layer 23 by chemical vapor deposition. Deposition is stopped when the thickness reaches half, and then only the pyrolytic carbon layer is deposited to form a gradient carbon layer.

[0027] (1) Place SiC fiber 21 into a CVD reactor, introduce methane under argon protection, adjust the reaction temperature to 900~1100℃ and the pressure to 0.1~0.3MPa, and keep it at that temperature for 2~4h. Under these conditions, introduce a mixed gas of carbon source and silicon source. The carbon source is methane (70~80% flow rate) and the silicon source is silicon tetrachloride (20~30% flow rate). The mixed gas undergoes a synergistic reaction at high temperature. On the one hand, the carbon source continues to decompose to produce carbon atoms, maintaining the continuous growth of the pyrolytic carbon layer. On the other hand, the silicon source reacts chemically with the carbon atoms decomposed from the carbon source. Since the reaction interface is the surface of the pure pyrolytic carbon layer, the generated SiC product is restricted by the pure pyrolytic carbon layer. In the pyrolytic carbon layer (0.5~1.5μm) near the SiC fiber 21, nano-SiC particles (5~50nm particle size) are generated in situ. The nano-SiC particles can hinder the overall graphitization of the carbon layer 23.

[0028] (2) Under argon protection, the temperature and pressure of the CVD reactor are kept constant. Methane is introduced under argon protection, and the reaction temperature is adjusted to 900~1100℃ and the pressure to 0.1~0.3MPa. The temperature is maintained for 2~4h. Under these conditions, the carbon source gas undergoes a thermal decomposition reaction on the surface of the SiC-containing carbon layer. Carbon atoms are uniformly deposited on the surface of the SiC-containing pyrolytic carbon layer, forming a high-purity pyrolytic carbon layer with a thickness of 0.5~1.5μm on the side close to the 2024Al matrix. Its function is to isolate the fiber from the subsequent reaction atmosphere and prevent the subsequently generated nano-SiC particles from directly adhering to the matrix surface, resulting in excessive interfacial bonding. At the same time, the flexibility of the high-purity pyrolytic carbon layer can buffer the difference in thermal expansion coefficients between the fiber and the matrix.

[0029] (3) After the reaction is complete, turn off the silicon source and carbon source, continue to introduce argon gas, and cool the reactor to room temperature at a cooling rate of 5~10℃ / min to avoid the agglomeration or oxidation of the nano-SiC particles generated at high temperature, and ensure the stability of the gradient carbon layer structure. This gradient carbon layer design avoids direct contact between SiC fiber 21 and 2024Al, and provides a carbon source for the subsequent formation of amorphous carbon layers.

[0030] In addition, this invention uses the average grain area (square micrometers (μm)) 2 The α-Al grain size was statistically analyzed. Since α-Al grains are polycrystalline structural units in the 2024Al alloy matrix 22, exhibiting irregular equiaxed or columnar crystal morphology, their influence on the material's mechanical properties depends more on the actual area occupied by the grains in the two-dimensional cross-section. For grains of the same diameter, the ability to impede dislocation movement differs significantly depending on whether the cross-sectional shape is elongated or equiaxed. Therefore, the α-Al grain size was calculated using μm. 2 The two-dimensional area parameter can more accurately reflect the actual shape and size distribution of the grains.

[0031] The present invention will now be further described in detail with reference to embodiments and accompanying drawings.

[0032] Example 1 (Room Temperature Tensile Properties Test) This embodiment sputtered SiC f The target material used for the 2024Al precursor wire 2 is a rolled 2024Al alloy target material. The total content of Mn, Si, and Fe impurities in the target material is less than 1 wt%, and the α-Al grains in the target material are equiaxed crystals with a size of less than 50 μm. 2 Before sputtering, the substrate (SiC fiber 21) was heated to 300°C and evacuated to a pressure of 5 × 10⁻⁶. -4 Pa. To ensure that the α-Al grain size in the precursor wire after sputtering is less than 20 μm. 2 The sputtering current was 2A, the sputtering voltage was 310V, and the total thickness of the sputtered coating (2024Al alloy substrate 22) was 25μm. The sputtered SiC... f The 2024Al precursor wire 2 was slowly cooled to room temperature at a cooling rate of 3℃ / min to reduce residual stress in the interface and matrix. In the sputtered 2024Al alloy matrix 22, the proportions of each alloying element were: Cu: 4.1, Mg: 1.5, Mn: 0.3, Si: 0.2, Fe: 0.1, Al: balance (wt%). A 2μm thick gradient carbon layer was designed on the surface of the SiC fiber 21. The pyrolytic carbon near the SiC fiber 21 contained nanoscale silicon carbide particles, and the silicon carbide particles in the carbon layer 23 accounted for 10% of the total mass. The carbon near the 2024Al alloy matrix 22 was high-purity (99.99wt%) pyrolytic carbon.

[0033] like Figure 3 As shown, the cladding material in this embodiment is 2024Al alloy, and the microstructure is mainly composed of fine equiaxed α-Al grains. The α-Al grains are equiaxed and have a size of less than 50 μm. 2Taking a small-sized rod as an example, the cladding diameter is 3.6 mm, the thickness is 0.5 mm, and the aperture is 2.6 mm. As the size of the aluminum-based composite material increases, the size of the cladding increases accordingly. The volume fraction of SiC fiber 21 is approximately 50%. The sputtered precursor wire is uniformly cut into equal-length segments, each 6 mm shorter than the cladding, with a length difference of less than 1 mm between each precursor wire to avoid compression and bending during installation. Then, it is inserted into the 2024Al alloy cladding 1, and the cladding cap is welded using a vacuum electron beam. The cap welding material is high-purity 2024Al alloy with an impurity content of less than 0.5 wt%.

[0034] The sample was heated to 420℃ at a heating rate of 6℃ / min and held at 120MPa for 3 hours. It was then cooled in the furnace to 200℃ and held at 120MPa for approximately 0.5 hours. Next, it was cooled in the furnace to 100℃, the pressure was adjusted to 100MPa, and held for approximately 0.5 hours. Finally, it was cooled in the furnace to room temperature to obtain a SiC fiber-reinforced aluminum matrix composite material. The microstructure of the 2024Al alloy matrix 22 and the 2024Al alloy cladding 1 were homogeneous. Only a 40nm amorphous carbon layer existed between the carbon layer 23 and the 2024Al alloy matrix 22, with no Al4C3 reaction products. f The 2024Al precursor fibers are evenly distributed in a hexagonal pattern, and the prepared sample has no broken SiC fibers 21.

[0035] In this embodiment, the microstructure of the 2024Al alloy matrix 22 and the 2024Al alloy cladding 1 after hot isostatic pressing are both composed of fine equiaxed α-Al, Al2Cu, and Al2CuMg phases that are alternately distributed. The thickness of the amorphous carbon layer at the interface is 40 nm, and the precursor filaments are arranged in equal hexagonal shapes. The prepared composite material has no fiber breakage inside.

[0036] like Figure 1 As shown, the hot isostatic pressing (HIP) specimen was processed into a rod-shaped tensile specimen with M6φ3 and L=21mm. The thread specification of the threaded portions at both ends of the specimen for connection with the mechanical testing machine fixture is M6. The connecting sections at both ends of the rod-shaped tensile specimen have M6 standard threads. The cross-sectional diameter of the effective tensile section is 3mm and the length is 21mm. φ1 corresponds to an effective tensile section diameter of 3mm, and φ2 corresponds to a cross-sectional diameter of 6mm for the connecting section. The surface of the processed specimen was polished with 150#, 800#, 2000#, and 3000# sandpaper, respectively. After polishing, the sample surface was smooth and without defects. The room temperature tensile properties were tested using a universal testing machine equipped with a mechanical extensometer. The test results show that the composite material has good room temperature tensile properties. The specific results are shown in Table 1. Table 1 shows the room temperature tensile properties. Material Tensile conditions Strength (MPa) Remark <![CDATA[SiC f / 2024Al]]> room temperature 1407 Tensile test (engineering) <![CDATA[SiC f / 2024Al]]> room temperature 1439 Tensile test (engineering) like Figure 4 As shown, the room temperature load displacement tensile curve shows that the interface between SiC fiber 21 and 2024Al matrix is ​​tightly bonded, and SiC fiber 21 and 2024Al matrix break almost simultaneously, ensuring that the strength is fully utilized. The performance target matches the data of the examples (such as the room temperature tensile strength of 1407MPa and 1439MPa in Example 1).

[0037] Example 2 (Room Temperature Compression Performance Test) This embodiment sputtered SiC f The target material used for the 2024Al precursor wire 2 is a rolled 2024Al alloy target material. The total content of Mn, Si, and Fe impurities in the target material is less than 1 wt%, and the α-Al grains in the target material are equiaxed crystals with a size of less than 50 μm. 2 Before sputtering, the substrate is heated to 230°C and evacuated to a pressure of 3 × 10⁻⁶. -4 Pa. To ensure that the α-Al grain size in the precursor wire after sputtering is less than 20 μm. 2 The sputtering current was 3A, the sputtering voltage was 330V, and the total thickness of the sputtered coating was 28μm. The sputtered SiC... f The 2024Al precursor wire 2 was slowly cooled to room temperature at a cooling rate of 4℃ / min to reduce residual stress in the interface and matrix. In the sputtered 2024Al alloy matrix 22, the proportions of each alloying element were: Cu: 4.1, Mg: 1.5, Mn: 0.3, Si: 0.2, Fe: 0.1, Al: balance (wt%). A 1μm thick gradient carbon layer was designed on the surface of the SiC fiber 21. The pyrolytic carbon near the SiC fiber 21 contained nanoscale silicon carbide particles, and the silicon carbide particles in the carbon layer 23 accounted for 6% of the total mass. The carbon near the 2024Al alloy matrix 22 was high-purity (99.99wt%) pyrolytic carbon.

[0038] like Figure 3 As shown, the cladding material in this embodiment is 2024Al alloy, and the microstructure is mainly composed of fine equiaxed α-Al grains. The α-Al grains are equiaxed and have a size of less than 50 μm. 2 Taking a small-sized rod as an example, the cladding diameter is 3mm, the thickness is 0.3mm, and the aperture is 2.4mm. As the size of the aluminum-based composite material increases, the size of the cladding increases accordingly. The volume fraction of SiC fiber 21 is approximately 50%. The sputtered precursor wire is uniformly cut into equal-length segments, each 4mm shorter than the cladding, with a length difference of less than 1mm between each wire to avoid compression and bending during installation. Then, it is inserted into the 2024Al alloy cladding 1, and the cladding cap is welded using a vacuum electron beam. The cap welding material is high-purity 2024Al alloy with an impurity content of less than 0.5wt%.

[0039] The sample was heated to 480℃ at a heating rate of 4℃ / min and held at 90MPa for 5 hours. It was then cooled in the furnace to 200℃ and held at 90MPa for approximately 2 hours. Next, it was cooled in the furnace to 100℃, the pressure was adjusted to 100MPa, and held for approximately 2 hours. Finally, it was cooled in the furnace to room temperature to obtain a SiC fiber-reinforced aluminum matrix composite material. The microstructure of the 2024Al alloy matrix 22 and the 2024Al alloy cladding 1 were homogeneous. Only a 20nm amorphous carbon layer existed between the carbon layer 23 and the 2024Al alloy matrix 22, with no Al4C3 reaction products. f The 2024Al precursor fibers are evenly distributed in a hexagonal pattern, and the prepared sample has no broken SiC fibers 21.

[0040] In this embodiment, the microstructure of the 2024Al alloy matrix 22 and the 2024Al alloy cladding 1 after hot isostatic pressing are both composed of fine equiaxed α-Al, Al2Cu, and Al2CuMg phases that are alternately distributed. The thickness of the amorphous carbon layer at the interface is 20 nm, and the precursor filaments are arranged in equal hexagonal shapes. The prepared composite material has no fiber breakage inside.

[0041] like Figure 2 As shown, the SiC fiber-reinforced aluminum matrix composite material is a multi-layered gradient composite structure. Continuous SiC fibers 21 serve as the reinforcing phase, and a carbon layer 23 achieves a gradient transition between the SiC fibers 21 and the 2024Al alloy matrix 22. Finally, it is encapsulated by a 2024Al alloy sheath 1. f The 2024Al precursor wire 2 is uniformly arranged in an isohyet (approximately 50% by volume) within the 2024Al alloy sheath 1, adjacent to SiC f The space between the two SiC precursor wires is filled with 2024Al alloy, free of porosity or fracture defects, ensuring uniform load distribution. f In the 2024Al precursor fiber 2, the interface between SiC fiber 21 and the 2024Al alloy matrix 22 is a carbon layer 23. Under hot isostatic pressing (HIP), carbon atoms from the pyrolytic carbon surface containing nano-sized silicon carbide particles near the 2024Al alloy matrix 22 slowly diffuse towards the surface of the 2024Al alloy matrix 22, accumulating to form an amorphous carbon layer. The rod-shaped compression specimen after HIP is processed into a cylindrical shape with a diameter of 3 mm and a length of 4.5 mm. The surface of the processed specimen was polished with 600#, 2000#, and 3000# sandpaper, respectively. The polished sample surface was smooth and defect-free. Then, the compressive properties were tested using a universal testing machine. The test results show that the composite material has good compressive properties, and the specific results are shown in Table 2. Table 2 shows the room temperature compression performance. Material Compression conditions Strength (MPa) Remark <![CDATA[SiC f / 2024Al]]> room temperature 3167 Compressed measured (engineering) <![CDATA[SiC f / 2024Al]]> room temperature 3009 Compressed measured (engineering) like Figure 5 As shown, the high compressive strength of the composite material is mainly achieved through the interaction of the encapsulation, matrix, and fiber interfaces. Under room temperature compressive loading, the interfacial bonding between SiC fiber 21 and the 2024Al matrix is ​​stable. The high stiffness of SiC fiber 21 can effectively resist compressive deformation, and the fine-grained structure of the 2024Al matrix (α-Al grains < 20 μm) further enhances its strength. 2 The grain boundaries impede dislocation movement, and the two work together to bear the compressive load, avoiding localized stress concentration caused by fiber agglomeration in traditional processes. In addition, the amorphous carbon transition layer of the gradient carbon layer can buffer compressive stress and prevent brittle delamination at the interface, ultimately giving the composite material high compressive strength.

[0042] Example 3 (High-Temperature Compression Performance Test at 200℃) This embodiment sputtered SiC f The target material used for the 2024Al precursor wire 2 is a rolled 2024Al alloy target material. The total content of Mn, Si, and Fe impurities in the target material is less than 1 wt%, and the α-Al grains in the target material are equiaxed crystals with a size of less than 50 μm. 2 Before sputtering, the substrate is heated to 380°C and evacuated to a pressure of 8 × 10⁻⁶. -4 Pa. To ensure that the α-Al grain size in the precursor wire after sputtering is less than 20 μm. 2 The sputtering current was 1A, the sputtering voltage was 300V, and the total thickness of the sputtered coating was 23μm. The sputtered SiC... f The 2024Al precursor wire 2 was slowly cooled to room temperature at a cooling rate of 2℃ / min to reduce residual stress in the interface and matrix. In the sputtered 2024Al alloy matrix 22, the proportions of each alloying element were: Cu: 4.1, Mg: 1.5, Mn: 0.3, Si: 0.2, Fe: 0.1, Al: balance (wt%). A 3μm thick gradient carbon layer was designed on the surface of the SiC fiber 21. The pyrolytic carbon near the SiC fiber 21 contained nanoscale silicon carbide particles, and the silicon carbide particles in the carbon layer 23 accounted for 13% of the total mass. The carbon near the 2024Al alloy matrix 22 was high-purity (99.99wt%) pyrolytic carbon.

[0043] like Figure 3 As shown, the cladding material in this embodiment is 2024Al alloy, and the microstructure is mainly composed of fine equiaxed α-Al grains. The α-Al grains are equiaxed and have a size of less than 50 μm. 2Taking a small-sized rod as an example, the cladding diameter is 4mm, the thickness is 0.6mm, and the aperture is 2.8mm. As the size of the aluminum-based composite material increases, the size of the cladding increases accordingly. The volume fraction of SiC fiber 21 is approximately 50%. The sputtered precursor wire is uniformly cut into equal-length segments, each 8mm shorter than the cladding, with a length difference of less than 1mm between each wire to avoid compression and bending during installation. Then, it is inserted into the 2024Al alloy cladding 1, and the cladding cap is welded using a vacuum electron beam. The cap welding material is high-purity 2024Al alloy with an impurity content of less than 0.5wt%.

[0044] The sample was heated to 460℃ at a heating rate of 5℃ / min and held at 100MPa for 4 hours. It was then cooled in the furnace to 200℃ and held at 100MPa for approximately 1 hour. Next, it was cooled in the furnace to 100℃, the pressure was adjusted to 100MPa, and held for approximately 1 hour. Finally, it was cooled in the furnace to room temperature to obtain a SiC fiber-reinforced aluminum matrix composite material. The microstructure of the 2024Al alloy matrix 22 and the 2024Al alloy cladding 1 were uniform, with only a 30nm amorphous carbon layer between the carbon layer 23 and the 2024Al alloy matrix 22, and no Al4C3 reaction products were observed. f The 2024Al precursor fibers are evenly distributed in a hexagonal pattern, and the prepared sample has no broken SiC fibers 21.

[0045] In this embodiment, the microstructure of the 2024Al alloy matrix 22 and the 2024Al alloy cladding 1 after hot isostatic pressing are both composed of fine equiaxed α-Al, Al2Cu, and Al2CuMg phases that are alternately distributed. The thickness of the amorphous carbon layer at the interface is 30 nm, and the precursor filaments are arranged in equal hexagonal shapes. The prepared composite material has no fiber breakage inside.

[0046] like Figure 2 As shown, the rod-shaped compression specimens after hot isostatic pressing were processed into cylindrical shapes with a diameter of 3 mm and a length of 4.5 mm. The surfaces of the processed specimens were polished with 600#, 2000#, and 3000# sandpaper, respectively, resulting in smooth and defect-free surfaces. The compressive properties at 200℃ were then tested using a universal testing machine. The test results show that the composite material exhibits good compressive properties at 200℃, as detailed in Table 3. Table 3 shows the high-temperature compression performance at 200℃. Material Compression conditions Strength (MPa) Remark <![CDATA[SiC f / 2024Al]]> 200℃ 2356 Compressed measured (engineering) <![CDATA[SiC f / 2024Al]]> 200℃ 2566 Compressed measured (engineering) like Figure 6As shown, at a high temperature of 200℃, the interfacial bonding between SiC fiber 21 and the 2024Al matrix remains stable. The amorphous carbon transition layer of the gradient carbon layer does not soften or oxidize at 200℃, effectively blocking further diffusion of Al atoms into SiC fiber 21 and preventing the formation of brittle interfacial phases (such as Al4C3) at high temperatures. The 2024Al matrix exhibits slightly improved plasticity at 200℃, while the amorphous carbon transition layer of the gradient carbon layer shows enhanced flexibility at high temperatures. This better buffers the thermal expansion difference between SiC fiber 21 and the 2024Al matrix, reducing interfacial stress concentration and enabling the composite material to maintain load stability even under higher displacements.

[0047] The results of the implementation show that the SiC fiber-reinforced aluminum matrix composite material of the present invention (SiC f The 2024Al alloy matrix (2024Al) consists of, from the inside out: SiC fiber 21, carbon layer 23, 2024Al alloy matrix 22, and 2024Al alloy cladding 1. Each layer is continuously distributed along the length of the SiC fiber 21, forming an integral structure with continuous axial reinforcement and radial gradient bonding. The 2024Al alloy cladding 1 has an equiaxed microstructure. The SiC fiber cladding and pilot wire are obtained through a hot isostatic pressing process. f / 2024Al composite material has a room temperature tensile strength of over 1400MPa, a room temperature compressive strength of over 3000MPa, and a 200℃ compressive strength of over 2300MPa, which significantly improves the room temperature tensile strength and high temperature compressive strength, and has a low cost, showing good application prospects.

[0048] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing SiC fiber-reinforced aluminum matrix composite material, characterized in that, Includes the following steps: Step 1: Preparation of SiC f / 2024Al precursor wire: using rolled 2024Al as the target material, the total content of Mn, Si, and Fe impurities in the target material is controlled to be <1wt%, and the α-Al grain size in the target material is <50μm. 2 Equiaxed crystals; before sputtering, the SiC fiber substrate is heated to 200~400℃ and evacuated to a pressure of 2×10⁻⁶. -4 ~9×10 -4 Pa; SiC fiber substrates were sputtered using a sputtering current of 1–4 A and a sputtering voltage of 290–340 V, controlling the total thickness of the sputtered 2024Al alloy matrix to be 20–29 μm, so that the α-Al grain size in the pre-sputtered wire was <20 μm. 2 After sputtering, the material is cooled to room temperature at a rate of 2~5℃ / min. Step 2, Sheath Assembly and Packaging: Using 2024Al alloy as the sheath material, the pilot wire obtained in Step 1 is cut into equal-length segments, each segment being 4-8 mm shorter than the sheath and the length difference between individual pilot wires being <1 mm. After the pilot wires are inserted into the sheath, the sheath cap is sealed using vacuum electron beam welding. The welding material is high-purity 2024Al alloy with an impurity content of <0.5 wt%, and the SiC fiber volume fraction is controlled at 50% ± 5%. Step 3, Segmented Hot Isostatic Pressing: The composite material encapsulated in Step 2 is heated to 400-500℃ at a heating rate of 4-7℃ / min and held at 80-130MPa for 3-5 hours; then cooled to 200℃ in the furnace and held at 80-130MPa for 0.5-2 hours; then cooled to 100℃ in the furnace and held at 100MPa for 0.5-2 hours; finally cooled to room temperature in the furnace to obtain SiC fiber reinforced aluminum matrix composite material.

2. The method for preparing SiC fiber-reinforced aluminum matrix composite material according to claim 1, characterized in that, In step one, the composition of the 2024Al alloy matrix obtained on the surface of SiC fiber after sputtering, by mass percentage, is: Cu 3~5%, Mg 1~2%, Mn 0~0.7%, Si 0~0.5%, Fe 0~0.3%, with Al as the balance.

3. The method for preparing SiC fiber-reinforced aluminum matrix composite material according to claim 2, characterized in that, The matrix composition of 2024Al alloy by mass percentage is: Cu 3.5~4.5%, Mg 1.2~1.8%, Mn 0~0.5%, Si 0~0.3%, Fe 0~0.1%, with Al as the balance.

4. The method for preparing SiC fiber-reinforced aluminum matrix composite material according to claim 1, characterized in that, In step one, a carbon layer with a thickness of 1~3μm is provided on the surface of SiC fiber. The carbon layer is located between SiC fiber and 2024Al alloy matrix. The side closer to SiC fiber is a pyrolytic carbon layer containing nanoscale silicon carbide particles. The mass ratio of silicon carbide particles in the carbon layer is 5~15%. The side closer to 2024Al alloy matrix is ​​a pyrolytic carbon layer.

5. The method for preparing SiC fiber-reinforced aluminum matrix composite material according to claim 1, characterized in that, In step two, the diameter of the sheath is 3~4mm, the thickness is 0.3~0.65mm, the aperture is 2.4~2.9mm, the size of the sheath increases accordingly as the size of the aluminum-based composite material increases, and the volume fraction of SiC fiber is 50%.

6. The method for preparing SiC fiber-reinforced aluminum matrix composite material according to claim 1, characterized in that, In SiC fiber-reinforced aluminum matrix composites, the microstructure of the 2024Al alloy matrix and the microstructure of the 2024Al alloy cladding are uniform, and there is an amorphous carbon layer with a thickness of 10~50nm between the carbon layer and the 2024Al alloy matrix, with no Al4C3 reaction products.

7. The method for preparing SiC fiber-reinforced aluminum matrix composite material according to claim 6, characterized in that, After hot isostatic pressing, both the matrix and cladding microstructures of the 2024Al alloy consist of alternating fine equiaxed α-Al, Al2Cu, and Al2CuMg phases. SiC f The 2024Al precursor fibers are evenly distributed in a hexagonal pattern, with no SiC fiber breakage.

Citation Information

Patent Citations

  • SiC-induced multi-phase reinforced aluminum-based composite material and preparation method thereof

    CN114525434A

  • Manufacturing equipment and manufacturing method of continuous SiC fiber reinforced Al-based composite wire

    CN116695031A

  • Method for improving plastic deformation capacity of aluminum matrix composite

    CN103643190A

  • Silicon carbide reinforced metal matrix composite with micro orientated structure and preparation method thereof

    CN108796262A

  • High volume fraction whisker reinforced 2024 aluminum-based composite sheath thermoforming method

    CN109596800A

Cited By

  • SiC fiber reinforced metal matrix composite material joint sample as well as preparation method and application thereof

    CN121720809A